2017
DOI: 10.1164/rccm.201610-1972oc
|View full text |Cite
|
Sign up to set email alerts
|

Volume-controlled Ventilation Does Not Prevent Injurious Inflation during Spontaneous Effort

Abstract: Limitation of Vt and Pl(es) by volume-controlled ventilation could not eliminate harm caused by spontaneous breathing unless the level of spontaneous effort was lowered and local dependent lung stress was reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 29 publications
1
88
2
3
Order By: Relevance
“…Growing evidence suggests that the presence of spontaneous breathing during mechanical ventilation is associated with several advantages, but may be harmful at the same time, particularly during the acute phase [1][2][3]. One of the possible mechanisms of injury Open Access *Correspondence: giacomo.bellani1@unimib.it 2 School of Medicine and Surgery, University of Milan-Bicocca, Monza, Italy Full list of author information is available at the end of the article associated with spontaneous breathing and assisted ventilation is the development of pendelluft [1].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that the presence of spontaneous breathing during mechanical ventilation is associated with several advantages, but may be harmful at the same time, particularly during the acute phase [1][2][3]. One of the possible mechanisms of injury Open Access *Correspondence: giacomo.bellani1@unimib.it 2 School of Medicine and Surgery, University of Milan-Bicocca, Monza, Italy Full list of author information is available at the end of the article associated with spontaneous breathing and assisted ventilation is the development of pendelluft [1].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies, however, were small (<50 patients/group), the intervention was not blinded and BPD not the primary outcome. This, combined with recent animal data suggesting that VTV might not eliminate lung injury during spontaneous breaths,24 raises questions whether the evidence that VTV is superior to other forms of respiratory support can already be regarded conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshida's study (18), however, found this is not the case in injured lungs. During spontaneous breathing, the tidal change in pleural pressure at dependent lung is significantly greater than at the middle lung (esophageal pressure).…”
Section: New Messages From Yoshida's Studymentioning
confidence: 82%
“…Of note, both high regional lung stress and "pendelluft" have been linked with lung injury by the same group of researchers (24). Moreover, the excessive regional lung stress at dependent lung was eliminated only when strenuous inspiratory effort was suppressed by paralysis in Yoshida's study (18). This may well be one of the reasons why eliminating spontaneous effort by administration of neuromuscular blocking agents at the early stage of ARDS can improve survival in patients who already received volume controlled ventilation (12).…”
Section: New Messages From Yoshida's Studymentioning
confidence: 89%
See 1 more Smart Citation